Effects of Simvastatin on Glucose Metabolism in Mouse MIN6 Cells - Jieqiong Zhou; Weihua Li; Qiang Xie; Yuxi Hou; Shaopeng Zhan; Xi Yang; Xiaofeng Xu; Jun Cai; Zhengrong Huang (Journal of Diabetes Research)
The aim of this study was to investigate the effects of simvastatin on insulin secretion in mouse MIN6 cells and the possible mechanism. MIN6 cells were, respectively, treated with 0 μM, 2 μM, 5 μM, and 10 μM simvastatin for 48 h. Radio immunoassay was performed to measure the effect of simvastatin on insulin secretion in MIN6 cells. Luciferase method was used to examine the content of ATP in MIN6 cells. Real-time PCR and western blotting were performed to measure the mRNA and protein levels of inward rectifier potassium channel 6.2 (Kir6.2), voltage-dependent calcium channel 1.2 (Cav1.2), and glucose transporter-2 (GLUT2), respectively. ATP-sensitive potassium current and L-type calcium current were recorded by whole-cell patch-clamp technique. The results showed that high concentrations of simvastatin (5 μM and 10 μM) significantly reduced the synthesis and secretion of insulin compared to control groups in MIN6 cells (P<0.05). ATP content in simvastatin-treated cells was lower than in control cells (P<0.05). Compared with control group, the mRNA and protein expression of Kir6.2 increased with treatment of simvastatin (P<0.05), and mRNA and protein expression of Cav1.2 and GLUT2 decreased in response to simvastatin (P<0.05). Moreover, simvastatin increased the ATP-sensitive potassium current and reduced the L-type calcium current. These results suggest that simvastatin inhibits the synthesis and secretion of insulin through a reduction in saccharometabolism in MIN6 cells.